Surgery for intra-abdominal abscess due to intestinal perforation caused by toothpick ingestion: Two case reports. Issue 36 (September 2019) - Lim, Dae Ro; Kuk, Jung Cheol; Kim, Taehyung; Shin, Eung Jin
Abstract: Rationale: Failure to pass though the gastrointestinal tract can result in inflammatory response, reactive fibrosis, and intestinal perforation. Fish bones, chicken bones, and toothpicks are the most common types of foreign substances that produce intestinal perforation during ingestion. Patient concerns: Case 1: A 49-year-old female was hospitalized with abdominal pain and a fever. The fever lasted for 5 days before hospitalization. Case 2: A 72-year-old male was hospitalized with abdominal pain and fever. The fever lasted for 4 days before hospitalization. Diagnoses: Case 1: An abdominal pelvic computed tomography (APCT) scan revealed a large inflammatory mass formation and linear high-density material within the inflammatory mass. The presence of foreign bodies, including acupuncture needles or intrauterine devices was ruled out. Case 2: An APCT scan revealed that there was a small abscess formation measuring about 2.5 cm abutting the abdominal wall and a parasitic infestation was ruled out. Interventions: Case 1: An exploratory laparotomy was performed. After removal of the abscess pocket, the sigmoid colon was found to be perforated, and there was a firm, sharp foreign body in the abscess pocket that measured about 5 cm and resembled a toothpick. Case 2: Laparoscopic exploration was then performed. When the abscess was removed from the abdominal wall using a harmony scalpel, a 4 cm foreign body that resembled a toothpick appeared in the abscess pocket. Outcomes: The patients recovered well after surgery and were discharged. Lessons: Two of the above case reports describe the cases in which the presence of toothpicks was suspected clinically, resulting in the surgery of intra-abdominal abscess caused by intestinal perforations.